Critical and independent role for SOCS3 in either myeloid or T cells in resistance to Mycobacterium tuberculosis. - Berit Carow (Public Library of Science (PLoS), 2013)
Suppressor of cytokine signalling 3 (SOCS3) negatively regulates STAT3 activation in response to several cytokines such as those in the gp130-containing IL-6 receptor family. Thus, SOCS3 may play a major role in immune responses to pathogens. In the present study, the role of SOCS3 in M. tuberculosis infection was examined. All Socs3(fl/fl) LysM cre, Socs3(fl/fl) lck cre (with SOCS3-deficient myeloid and lymphoid cells, respectively) and gp130(F/F) mice, with a mutation in gp130 that impedes binding to SOCS3, showed increased susceptibility to infection with M. tuberculosis. SOCS3 binding to gp130 in myeloid cells conveyed resistance to M. tuberculosis infection via the regulation of IL-6/STAT3 signalling. SOCS3 was redundant for mycobacterial control by macrophages in vitro. Instead, SOCS3 expression in infected macrophages and DCs prevented the IL-6-mediated inhibition of TNF and IL-12 secretion and contributed to a timely CD4+ cell-dependent IFN-γ expression in vivo. In T cells, SOCS3 expression was essential for a gp130-independent control of infection with M. tuberculosis, but was neither required for the control of infection with attenuated M. bovis BCG nor for M. tuberculosis in BCG-vaccinated mice. Socs3(fl/fl) lck cre mice showed an increased frequency of γδ+ T cells in different organs and an enhanced secretion of IL-17 by γδ+ T cells in response to infection. Socs3(fl/fl) lck cre γδ+ T cells impaired the control of infection with M. tuberculosis. Thus, SOCS3 expression in either lymphoid or myeloid cells is essential for resistance against M. tuberculosis via discrete mechanisms.